2017
DOI: 10.1080/00927872.2017.1346772
|View full text |Cite
|
Sign up to set email alerts
|

On one-relator products induced by generalized triangle groups II

Abstract: In this paper we study a group G which is the quotient of a free product of groups by the normal closure of a word that is contained in a in a subgroup which has the form of a generalised triangle group. We use known properties of generalised triangle groups, together with detailed analyses of pictures and of words in free monoids, to prove a number of results such as a Freiheitssatz and the existence of Mayer-Vietoris sequences for such groups under suitable hypotheses. The hypotheses are weaker than those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…We also mention that the case when m = 2 is largely open. For partial results in this case see [5,1,2]. The aim of this paper is to extend the result in [4] by allowing to an extent letters of order 2 in R. In [4] it was shown that R m satisfies the small cancellation condition C(2m) when D 2 (S R ) = 0, which is essentially an observation in [11].…”
Section: Preliminariesmentioning
confidence: 78%
See 3 more Smart Citations
“…We also mention that the case when m = 2 is largely open. For partial results in this case see [5,1,2]. The aim of this paper is to extend the result in [4] by allowing to an extent letters of order 2 in R. In [4] it was shown that R m satisfies the small cancellation condition C(2m) when D 2 (S R ) = 0, which is essentially an observation in [11].…”
Section: Preliminariesmentioning
confidence: 78%
“…In Section section 3 we prove a number of lemmas about word combinatorics and pictures. These lemmas are then used to deduce Theorems [1][2]. In Section section 4 we deduce a number of applications of our results.…”
Section: Theorem 2 Let R Be a Cyclically Reduced Word In The Free Prmentioning
confidence: 87%
See 2 more Smart Citations
“…We also mention that the case when m = 2 is largely open. For partial results in this case see [9,10,11]. The aim of this paper is to extend the result in [7] by allowing letters of order 2 in R. Also we require results about pictures over G, in particular the fact that R m satisfies the small cancellation condition C(2m) when R has a certain form.…”
Section: Preliminariesmentioning
confidence: 99%